2018
DOI: 10.3390/math6110222
|View full text |Cite
|
Sign up to set email alerts
|

A New Version of the Generalized Krätzel–Fox Integral Operators

Abstract: This article deals with some variants of Krätzel integral operators involving Fox’s H-function and their extension to classes of distributions and spaces of Boehmians. For real numbers a and b > 0 , the Fréchet space H a , b of testing functions has been identified as a subspace of certain Boehmian spaces. To establish the Boehmian spaces, two convolution products and some related axioms are established. The generalized variant of the cited Krätzel-Fox integral operator is well defined and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, the notion of primal is the dual structure of grill. Furthermore, some new studies have been revealed regarding primal topological spaces in [2,3,4,5] since the introduction of primal.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the notion of primal is the dual structure of grill. Furthermore, some new studies have been revealed regarding primal topological spaces in [2,3,4,5] since the introduction of primal.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these functions were introduced to solve specific problems and some others were used to solve general problems. In recent years, generalized and multivariable forms of special functions of mathematical physics have also undergone significant evolutions (see [1][2][3][4][5][6][7][8][9][10][11][12] for more details). The theory of orthogonal polynomials and special functions is of intrinsic interest to many parts of mathematics.…”
Section: Introductionmentioning
confidence: 99%
“…where (γ ) n is the Pochhammer symbol (see [21] p. 2 and pp. [4][5][6] and Γ (•) is the gamma function (see [21] Sect. 1.1), with the two auxiliary functions…”
Section: Definition 11 Wright Introduced the Classical Wright Functionmentioning
confidence: 99%